2018
DOI: 10.1080/09712119.2018.1505619
|View full text |Cite
|
Sign up to set email alerts
|

Effect of threonine and potassium carbonate supplementation on performance, immune response and bone parameters of broiler chickens

Abstract: This study aimed to investigate the effect of different levels of dietary threonine (i.e. 100%, 110% and 120% of Ross recommendations) and potassium (i.e. 0.85% and 0.94% of diet) on performance, immune response, and bone parameters broiler chickens. Three hundred one-day-old male broiler chickens (Ross 308) were randomly assigned to 1 of 6 dietary treatments in a completely randomized design with a 3 × 2 factorial arrangement. Growth performance was not affected by dietary treatments. Birds fed diet containin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 38 publications
1
3
0
Order By: Relevance
“…The accelerated growth performance observed in the broilers consuming Thr supplemented diets, additionally, because of its role in synthesis of protein and maintenance of body protein turnover (Ton et al, 2013 ). These findings are in agreement with a few recent findings in broilers (Shirzadegan et al, 2015 ; Min et al, 2017 ; Zarrin-Kavyani et al, 2018 ). Min et al ( 2017 ) reported a significant quadratic increase in average daily gain and a quadratic decrease in FCR during the whole experiment (0 to 42 d) with the increase of Thr from 85 to 150% of NRC recommendations.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The accelerated growth performance observed in the broilers consuming Thr supplemented diets, additionally, because of its role in synthesis of protein and maintenance of body protein turnover (Ton et al, 2013 ). These findings are in agreement with a few recent findings in broilers (Shirzadegan et al, 2015 ; Min et al, 2017 ; Zarrin-Kavyani et al, 2018 ). Min et al ( 2017 ) reported a significant quadratic increase in average daily gain and a quadratic decrease in FCR during the whole experiment (0 to 42 d) with the increase of Thr from 85 to 150% of NRC recommendations.…”
Section: Discussionsupporting
confidence: 93%
“…An improved growth performance in broilers fed diets containing higher, above NRC recommended, levels of d-Thr may be due to more amount of d-Thr available to satisfy optimum Thr requirement for growth and the gut, which resulted in an improved gut health (Table 4 ) consequently enhanced AIDP and AA (Table 5 ) compared with those fed recommeneded level. Zarrin-Kavyani et al ( 2018 ) observed an improved FI during grower and a higher BW during grower and entire experimental period, whereas a better FCR during the starter period in broilers fed 10% extra Thr in comparison with those consuming the control diet. Shirzadegan et al ( 2015 ), similarly, observed a higher BWG, during the grower as well as over the entire experimental phase, in broilers fed 0.75% d-Thr than that of 0.5% and 1.0% dietary Thr.…”
Section: Discussionmentioning
confidence: 97%
“…Similarly, it was reported that potassium acetate increased antibody production on a per cell basis (Fong et al., 1997). In another study, it was showed that potassium supplementation in broiler chicken results in elevation of lymphocyte percentage (Zarrin‐Kavyani et al., 2018). These reports are in agreement with the results of the present study which shows higher values of IgG in calves supplemented with both extracts compared with the calves of groups 1 and 3.…”
Section: Discussionmentioning
confidence: 99%
“…for immune responses (Runge, Blackall, & Casey, 2007). Threonine (T) is the third limiting AA after lysine and methionine in conventional poultry diets and is required for mucin synthesis as part of the intestinal immune function, inhibition of apoptosis, stimulation of lymphocyte proliferation and enhancement of antibody production (Zarrin-Kavyani, Khatibjoo, Fattahnia, & Taherpour, 2018). Also, arginine (A) and glutamine (G) supplementation may have beneficial effects on performance and immune function under normal rearing conditions (Murakami, Fernandes, Hernandes, & Santos, 2012).…”
Section: Introductionmentioning
confidence: 99%